Ab initio simulations of α‐ and β‐ammonium carbamate (NH4·NH2CO2), and the thermal expansivity of deuterated α‐ammonium carbamate from 4.2 to 180 K by neutron powder diffraction. Issue 3 (4th May 2022) - Howard, Christopher M.; Wood, Ian G.; Knight, Kevin S.; Fortes, A. Dominic
Abstract : The results of ab initio simulations carried out using density functional theory on two polymorphs of ammonium carbamate are reported. Also reported is a refined crystal structure of deuterated α‐ammonium carbamate from high‐resolution neutron powder diffraction data, with thermal expansion measurements from 4.2 to 180 K. Abstract : Experimental and computational studies of ammonium carbamate have been carried out, with the objective of studying the elastic anisotropy of the framework manifested in (i) the thermal expansion and (ii) the compressibility; furthermore, the relative thermodynamic stability of the two known polymorphs has been evaluated computationally. Using high‐resolution neutron powder diffraction data, the crystal structure of α‐ammonium carbamate (ND4 ·ND2 CO2 ) has been refined [space group Pbca, Z = 8, with a = 17.05189 (15), b = 6.43531 (7), c = 6.68093 (7) Å and V = 733.126 (9) Å 3 at 4.2 K] and the thermal expansivity of α‐ammonium carbamate has been measured over the temperature range 4.2–180 K. The expansivity shows a high degree of anisotropy, with the b axis most expandable. The ab initio computational studies were carried out on the α‐ and β‐polymorphs of ammonium carbamate using density functional theory. Fitting equations of state to the P ( V ) points of the simulations (run athermally) gave the following values: V 0 = 744 (2) Å 3 and bulk modulus K 0 = 16.5 (4) GPa for the α‐polymorph, and V 0 = 713.6 (5) Å 3 and K 0 = 24.4 (4) GPa for the β‐polymorph. The simulations show good agreement with the thermoelastic behaviour of α‐ammonium carbamate. Both phases show a high‐degree of anisotropy; in particular, α‐ammonium carbamate shows unusual compressive behaviour, being determined to have negative linear compressibility (NLC) along its a axis above 5 GPa. The thermodynamically stable phase at ambient pressure is the α‐polymorph, with a calculated enthalpy difference with respect to the β‐polymorph of 0.399 kJ mol −1 ; a transition to the β‐polymorph could occur at ∼0.4 GPa.